The Lifespan of Smooth Solutions to Semilinear Wave Equations in Schwarzschild Space-Time (Journal of Partial Differential Equations, 2023)
This paper considers the Cauchy problem of the semilinear wave equationswith small initial data in the Schwarzschild space-time, $□_gu = |u_t| ^p,$ where $g$ denotesthe Schwarzschild metric. When $1< p